2008
DOI: 10.1016/j.jpcs.2007.10.138
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of transdermal delivery using magainin pore-forming peptide

Abstract: The skin's outer layer of stratum corneum, which is a thin tissue containing multilamellar lipid bilayers, is the main barrier to drug delivery to the skin. To increase skin permeability, our previous work has shown large enhancement of transdermal permeation using a pore-forming peptide, magainin, which was formulated with N-lauroyl sarcosine (NLS) in 50% ethanol-in-PBS. Mechanistic analysis suggested that magainin and NLS can increase skin permeability by disrupting stratum corneum lipid structure. In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 10 publications
(7 reference statements)
1
7
0
Order By: Relevance
“…The screening of the attractive electrostatic interaction by such a small change in the Debye length implies that the fluorescein molecule must be close to the edge of this pathway. This is consistent with our previous finding that magainin did not enhance transdermal transport of molecules larger than fluorescein (Kim et al,2008), such as calcein (623 Da, r = 6 Å and dextran (3,000 Da, r = 16 Å (Oliver et al, 1992). This is also consistent with previous studies of magainin in simpler lipid bilayer systems, in which the pores are believed to be of Angstrom dimensions (Ludtke et al, 1995, Matsuzaki et al, 1996.…”
Section: Debye Length Calculationssupporting
confidence: 93%
“…The screening of the attractive electrostatic interaction by such a small change in the Debye length implies that the fluorescein molecule must be close to the edge of this pathway. This is consistent with our previous finding that magainin did not enhance transdermal transport of molecules larger than fluorescein (Kim et al,2008), such as calcein (623 Da, r = 6 Å and dextran (3,000 Da, r = 16 Å (Oliver et al, 1992). This is also consistent with previous studies of magainin in simpler lipid bilayer systems, in which the pores are believed to be of Angstrom dimensions (Ludtke et al, 1995, Matsuzaki et al, 1996.…”
Section: Debye Length Calculationssupporting
confidence: 93%
“…One such peptide used to enhance skin permeability is magainin, a 23-amino acid peptide known to form pores in bacterial cell membranes [151,152]. While previously demonstrated to increase the permeability of small molecules, its use for peptide delivery enhancement still requires optimization [153]. In addition, recent, work by Ruan et al .…”
Section: Biochemical Enhancementmentioning
confidence: 99%
“…For example, we previously observed that increased skin permeability was strongly dependent on magainin concentration. 23 As shown in Figure 6(A), increasing magainin concentration up to 1 mM increased skin permeability (ANOVA, p < 0 05). However, further increase in magainin concentration to 2 mM reduced enhancement below that of the NLS control, as reported previously.…”
Section: Effect Of Peptide Concentration On Skin Permeabilitymentioning
confidence: 73%
“…However, further increase in magainin concentration to 2 mM reduced enhancement below that of the NLS control, as reported previously. 23 This effect may be explained by aggregation of high-concentration magainin in the stratum corneum lipids, which may disrupt and occlude the expected pore structures formed by lower-concentration magainin. 24 Transdermal Delivery Enhanced by Antimicrobial Peptides Kim et al In order to investigate the correlation of enhancement with lipid structure disruption, we measure FTIR spectra to assess lipid fluidity.…”
Section: Effect Of Peptide Concentration On Skin Permeabilitymentioning
confidence: 99%